Raman mapping of fentanyl transdermal delivery systems with off-label modifications. Issue 3 (11th December 2019) - Xu, Teng; Yilmaz, Huzeyfe; Willett, Daniel R.; Strasinger, Caroline; Rodriguez, Jason D.; Keire, David A.; Wokovich, Anna M.
Abstract : Raman mapping and chemometric models were used to characterize crystal formation in fentanyl transdermal delivery systems resulting from off-label modifications. Abstract : Raman mapping is a powerful and emerging tool in characterization of pharmaceuticals and provides non-destructive chemical and structural identification with minimal sample preparation. One pharmaceutical form that is suitable but has not been studied in-depth with Raman mapping is transdermal delivery systems (TDS). TDS are dosage forms designed to deliver a therapeutically effective amount of active pharmaceutical ingredient (API) across a patient's skin. To enhance drug delivery through the skin, the API in the formulation is often close to a saturated or supersaturated state. Thus, improper use or off-label modifications can lead to occurrence of unwanted API changes, specifically, crystallization over time. Here, off-label modifications were mimicked on a set of fentanyl drug-in-adhesive TDS sold on the U.S. market by four different manufacturers via die cutting, and then the die cut TDS were investigated through confocal Raman mapping for structural and chemical changes. Using Multivariate Curve Resolution (MCR), not only was morphological and chemical characterization of transdermal systems provided, but also fentanyl crystals in certain products due to off-label modifications were identified. The chemometric model used in analysis of Raman maps allowed precise identification of fentanyl as the crystalline material as confirmed by the hit-quality-index correlation of component spectra from the chemometric model with library spectra of a fentanyl reference standard. The results show that confocal Raman mapping with MCR can be utilized in assessing pharmaceutical quality of TDS. This method has the potential to be widely used in characterization of such systems as an alternative to existing techniques.